When women ruled the Pacific : power and politics in nineteenth-century Tahiti and Hawai'i - Schulz, Joy (Studies in Pacific worlds., 2023)
Joy Schulz explores Polynesia's nineteenth-century women rulers, who held enormous domestic and foreign power and expertly governed their people amid shifting loyalties, outright betrayals, and the ascendancy of imperial racism.